2008
DOI: 10.1186/bf03352848
|View full text |Cite
|
Sign up to set email alerts
|

Fault models of unusual tsunami in the 17th century along the Kuril trench

Abstract: Geologic evidence has shown that unusual tsunami deposits are traced as high as 18 m above the current sea level or as far as 1-4 km inland from the shoreline on the Pacific coast of eastern Hokkaido, and that such unusual tsunamis have recurred at about 500 year interval with the most recent event in the 17th century. We computed coastal tsunami heights along the Hokkaido and Sanriku coasts and inundation at five coastal marshes in Hokkaido where the tsunami deposits were mapped. Three types of faults were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…It was concordant with the segment boundary for large earthquakes proposed by Tokachi-oki earthquakes represent the area of more than 1 m of slip estimated by Satake et al (2006) and Tanioka et al (2004), respectively. The areas for the 1969 Shikotan-oki earthquake and the huge earthquakes in 17th century represent rectangular faults estimated by Fukao and Furumoto (1975) and Satake et al (2008). Utsu (1972) (Fig.…”
Section: Slip Distribution Of the 1973 Nemuro-oki Earth-mentioning
confidence: 99%
See 1 more Smart Citation
“…It was concordant with the segment boundary for large earthquakes proposed by Tokachi-oki earthquakes represent the area of more than 1 m of slip estimated by Satake et al (2006) and Tanioka et al (2004), respectively. The areas for the 1969 Shikotan-oki earthquake and the huge earthquakes in 17th century represent rectangular faults estimated by Fukao and Furumoto (1975) and Satake et al (2008). Utsu (1972) (Fig.…”
Section: Slip Distribution Of the 1973 Nemuro-oki Earth-mentioning
confidence: 99%
“…In addition to these M ∼ 8 historical earthquakes, geological studies of tsunami deposits along the southern coast of Hokkaido suggest that a huge earthquake with M > 8.5 ruptured both the Tokachi-oki and Nemuro-oki segments in the 17th century (Nanayama et al, 2003;Satake et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The observed data indicated that smallto-moderate-magnitude earthquakes were extremely infrequent in the Nankai source regions. Simultaneous rupturing of regions off Tokachi and off Nemuro was also inferred (e.g., Hirakawa, 2000a, b;Nanayama et al, 2003;Satake et al, 2008). The recurrence period of the Tokachi-Nemuro earthquake was estimated as 400 to 500 years, and it is inferred that the most recent one occurred during the 17th century from the tsunami deposits along the eastern coastal line of Hokkaido.…”
Section: Seismicity In the Nankai Source Regionmentioning
confidence: 97%
“…The recurrence period of the Tokachi-Nemuro earthquake was estimated as 400 to 500 years, and it is inferred that the most recent one occurred during the 17th century from the tsunami deposits along the eastern coastal line of Hokkaido. The tsunami magnitude of the Tokachi-Nemuro earthquake was estimated as 9.0 (Abe, personal communication, 2002) based on estimated tsunami inundation heights of 10-15 m, although Satake et al (2008)'s estimate of M w was 8.5. The result (Fig.…”
Section: Seismicity In the Nankai Source Regionmentioning
confidence: 99%
“…During the past several decades, various geophysical methods and datasets have been used to understand the mechanisms behind these devastating earthquakes, including seismic and geodetic ground motion datasets (Mazzotti et al, 2000;Kawasaki et al, 2001;Koyama et al, 2004;Hashimoto et al, 2009;Igarashi, 2010;Katsumata, 2011;Uchida and Matsuzawa, 2011), historical tsunami deposits (Minoura et al, 2001;Satake et al, 2008), aftershock distributions (Katsumata et al, 1995), and seafloor bathymetry (Umino et al, 1990;Tanioka et al, 1997;Tsuji et al, 2011). The most traditional method is to evaluate the coupling on the subduction thrust faults by calculating the ratio of the observed to the expected moment release rate (Ruff and Kanamori, 1980;Peterson and Seno, 1984; Copyright c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences; TERRAPUB.…”
Section: Introductionmentioning
confidence: 99%